Diffuse myocardial fibrosis in adolescents operated with arterial switch for transposition of the great arteries - A CMR study. (1st February 2019) - Suther, K.R.; Hopp, E.; Geier, O.; Brun, H.; Nguyen, B.; Tomterstad, A.H.; Smevik, B.; Fiane, A.E.; Lindberg, H.L.; de Lange, C.
Highlights: CMR reveals signs of diffuse myocardial fibrosis in young ASO TGA patients. Extracellular volume fraction was higher in patients compared to controls. MR marker of diffuse myocardial fibrosis was increased in all coronary territories.